Testing and Characterization of Sustainable Innovative Bituminous Materials and Systems State-of-the-Art Report of the RILEM Technical Committee 237-SIB - Partl, Manfred N.; Porot, Laurent; Di Benedetto, Hervé; Canestrari, Francesco; Marsac, Paul.; Tebaldi, Gabriele; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents the detailed results of five task groups of the RILEM technical committee TC 237-SIB on Testing and Characterization of Sustainable Innovative Bituminous Materials and Systems. It concentrates on specific new topics in asphalt binder and mixture testing, dealing with new developments in asphalt testing, in particular also in view of new innovative bituminous materials, such as hot and cold recycled mixtures, grid reinforced pavements and recycled Reclaimed Asphalt Pavements (RAP), where test methods developed for traditional asphalt concrete are not a priori applicable. The main objective is providing a basis for pre-standardization by comparing different test methods and showing ways for fundamental improvements. Thus, the book also points the way for a further advanced chemo-physical understanding of materials and their role in pavement systems relying on fundamental material properties and suitable models for describing and predicting the intrinsic mechanisms thatdetermine the material behavior. .
Preface -- Acknowledgement -- Chapter 1 Introduction, by Manfred N. Partl -- Chapter 2 Bituminous Binder, by Laurent Porot, Hilde Soenen, Jeroen Besamusca, Alex Apeagyei, James Grenfell, Stefan Vansteenkiste, Emmanuel Chailleux, Vincent Gaudefroy, Preeda Chaturabong, Cristina Tozzo, Ignacio Artamendi, Darius Sybilski, Francisco Barcelo Martinez, Said Safwat, Manfred Partl, Francesco Canestrari, Elisabeth Hauser, Michael Wistuba -- Chapter 3 Three-dimensional characterisation of linear viscoelastic properties of bituminous mixtures, by A. Graziani, H. Di Benedetto, D. Perraton, C. Sauzéat, B. Hofko, Q.T. Nguyen, S. Pouget, L. D. Poulikakos, N. Tapsoba, J. Grenfell, A. Cannone Falchetto, M. Wistuba, C. Petit -- Chapter 4 Advanced Interface Testing of Grids in Asphalt Pavements, by Francesco Canestrari, Antonio D'Andrea, Gilda Ferrotti, Andrea Graziani, Manfred N. Partl, Christophe Petit, Christiane Raab, Cesare Sangiorgi -- Chapter 5 Recycling, by Paul Marsac, Wim Van den bergh, Nathalie Piérard, James Grenfell, Thomas Gabet, Virginie Mouillet, Laurent Porot, Miguel Perez Martinez, Fabienne Farcas -- Chapter 6 Cold Recycling of Reclaimed Asphalt Pavements, by Gabriele Tebaldi, Eshan Dave, Martin Hugener, Augusto Cannone Falchetto, Daniel Perraton, Andrea Grilli, Davide Lo Presti, Marco Pasetto, Andreas Loizos, Kim Jenkins, Alex Apeagyei, James Grenfell, Maurizio Bocci -- Index.  .
Keywords: Building materials; Materials -- Analysis; Mechanics, Applied; Solids; Building Materials; Characterization and Analytical Technique; Solid Mechanics